2021
DOI: 10.3390/jof7030218
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and N2O Production Potential of Fungi in an Oceanic Oxygen Minimum Zone

Abstract: Fungi in terrestrial environments are known to play a key role in carbon and nitrogen biogeochemistry and exhibit high diversity. In contrast, the diversity and function of fungi in the ocean has remained underexplored and largely neglected. In the eastern tropical North Pacific oxygen minimum zone, we examined the fungal diversity by sequencing the internal transcribed spacer region 2 (ITS2) and mining a metagenome dataset collected from the same region. Additionally, we coupled 15N-tracer experiments with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 60 publications
1
47
2
Order By: Relevance
“…Using different techniques, fungi have been found in other lowoxygen marine environments including the coastal upwelling system of Peru (hyphal chitin staining; Gutiérrez et al 2011), and in anoxic sediments of the Arabian Sea (Stief et al 2014). Recently, Peng and Valentine (2021) evaluated the diversity of free living and particle-associated (> 22 μm) fungi in the ETNP ODZ, also finding fungi to be dominated by Basidiomycota and Ascomycota at most depths, consistent with our de novodiscovery results.…”
Section: Fungal Peptidessupporting
confidence: 86%
See 1 more Smart Citation
“…Using different techniques, fungi have been found in other lowoxygen marine environments including the coastal upwelling system of Peru (hyphal chitin staining; Gutiérrez et al 2011), and in anoxic sediments of the Arabian Sea (Stief et al 2014). Recently, Peng and Valentine (2021) evaluated the diversity of free living and particle-associated (> 22 μm) fungi in the ETNP ODZ, also finding fungi to be dominated by Basidiomycota and Ascomycota at most depths, consistent with our de novodiscovery results.…”
Section: Fungal Peptidessupporting
confidence: 86%
“…Peptides specifically identifying the filamentous genus Aspergillus were found in all samples of this study except the deepest suspended POM (Table S7), as were numerous other filamentous and hyphae-producing groups of fungi and nonfungi (Actinobacteria, Oomycota). Although it is unknown how important fungal nitrogen cycling may be in the water column of the ODZ, Peng and Valentine (2021) recently demonstrated using 15 N-tracer incubations that fungal N 2 O production peaked at the upper oxic-anoxic interface in the ENTP ODZ water column. Our findings demonstrate that fungal peptides can be extracted and identified from marine POM via metaproteomic techniques.…”
Section: Fungal Peptidesmentioning
confidence: 99%
“…Our data indicate that fungi can constitute up to 18% of the microbial community in the PM10 part of the air microbiome. This ratio is one to two orders of magnitude higher than what has been reported for the water column of the open ocean, where fungal reads were up to 0.2% of the total metagenomes [62]. This difference suggests that atmospheric transport is a potential mechanism for fungal dispersal from land to sea, an idea that has been suggested for bacterial dispersal [8,24], and is consistent with the positive correlation between the relative abundance of bacterial/archaeal reads and PM10 concentrations in this study (Figure 2).…”
Section: Discussioncontrasting
confidence: 55%
“…Peng and Valentine (2021) recently suggested a potential niche for fungal denitrification in the ETNP at 0.0 < [O 2 ] < 0.93 μM and found that it contributes significantly to N 2 O production in the water column. Because fungi produce N 2 O with an SP ranging from ∼15‰ to ∼37‰ (Maeda et al., 2015; Rohe et al., 2014; Sutka et al., 2008), fungal denitrification could partly account for inferred N 2 O production via denitrification with a nonzero SP.…”
Section: Discussionmentioning
confidence: 99%